Patient use of an online triage platform: a mixed-methods retrospective exploration in UK primary care - Eccles, Abi (Br J Gen Pract, 2019)
BACKGROUND: Recent years have seen the introduction of online triage allowing patients to describe their problem via an online form. Subsequently, a GP telephones the patient, conducting a telephone consultation or arranging a face-to-face consultation. AIM: This study aimed to explore patterns-of-use and patients’ experiences of using an online triage system. DESIGN AND SETTING: This retrospective study analysed routinely collected data (from all practices using the ‘askmyGP’ platform for the duration of the study period, 19 May 2017 to 31 July 2017), using both quantitative and qualitative approaches. Data originated from an online triaging platform used by patients in nine general practices across the UK. METHOD: Data from 5447 patients were quantitatively analysed to describe characteristics of users, patterns-of-use, and reasons given by patients for using the platform. Free-text comments left by patients (n = 569) on their experience of use were qualitatively analysed. RESULTS: Highest levels of use were observed in females (65.5%, n = 3570) and those aged 25–34 years. Patterns of use were high between 0800 and 0959, and on Mondays and Tuesdays. Use outside of GP practice opening hours was low. Common reasons for using the platform were for medication-related enquiries, for administrative requests, and to report a specific symptom. Comments left by patients suggested advantages to using the platform, for example, convenience and the written format, but these did not extend to all users. CONCLUSION: Patterns-of-use and patient types were in line with typical contacts to GP practices. Though the age of users was broad, highest levels of use were from younger patients. The perceived advantages to using online triage, such as convenience and ease of use, are often context dependent.